Impact of Inflation on Economic Growth: Evidence from Tanzania - Maiga, Yohana (Journal of Agricultural Studies, 2024)
This empirical study investigates the impact of inflation on economic growth in Tanzania, aiming to provide insights for policymakers on maintaining macroeconomic stability. Utilizing a quantitative research design, the study analyzes secondary data spanning 32 years (1990-2021) through reduced-form regression and co-integration analysis techniques. The findings reveal a significant negative correlation between inflation and economic growth, indicating that higher inflation rates are associated with lower GDP growth. However, no long-term relationship or co-integration between inflation and economic growth is found. This study contributes to the existing literature by providing empirical evidence on the negative impact of inflation on economic growth in Tanzania, emphasizing the importance of price stability for sustainable economic growth. The findings underscore the need for policymakers to prioritize effective monetary policies while promoting investment and productivity to ensure sustained economic growth.